CHEMICAL STUDY OF FLAVONS AND FLAVONOLS COMPOSITION IN PROPOLIS - E. V. Lupina; D. I. Pisarev; O. O. Novikov; A. Yu. Malyutina; G. V. Vasilev; Yu. G. Vasileva (Фармация и фармакология (Пятигорск))
The aim of the study. This article is dedicated to the comparative assessment of flavones and flavonols composition in various samples of propolis for providing the possibility of its standardization. Materials and methods. To carry out the research, 6 experimental samples of propolis were taken from different regions of Russia. Using those samples, we prepared the extracts with 80% ethanol according to traditional scheme of making tinctures in the ratio of 1:10. After that our extracts were filtered and used directly in the assessment. Chromatographic separation of spirit extracts of propolis was carried out on a liquid chromatograph of “Agilent Technologies 1200 Infinity”, USA. The detection was carried out on the basis of the diode array detector “Agilent 1200”. Results and discussion. Using the reversed-phase HPLC in gradient elution regime we managed to identify flavonols and flavones. It was found out that the composition of propolis has a stable composition of flavones and flavonols including quercetin, isoramnetin, 3,4’-dimethoxycempferol, ramnetin, penduletin, kaempferol, ramnocitrin, galangin, kaempherid, chrysin and methoxyhalangin. Among the identified components, the highest content is in flavonols, methoxyl derivatives ramnocitrin (22,0%), and kaempherid (12,0%); in flavones it is chrysin(16,0%). The specific gravity of each component within the specified group was calculated by the internal normalization method. It was established that about 84% of all flavonols are in kaempferol and its methoxyl derivatives. The composition of flavones and flavonols can vary depending on the sample. Hereby, kempferol was identified in all the studied samples, whereas some of the identified components were absent from separate propolis samples. Propolis standardization by method of high-performance liquid chromatography in respect of the content of flavonoids in terms of kaempferol as a stable, commercially most available component of propolis was suggested. With the use of absolute calibration, the quantitative content of kaempferol in propolis samples wasdetermined in the range of 0.0141-0.0159%. Conclusion. The results of the carried out experiments made it possible to recommend the quality assessment of propolis according to the content of kaempferol in the experimental samples.